GEOLOGI, ALTERASI DAN MINERALISASI DAERAH SUMBERMANJING WETAN DAN SEKITARNYA, KABUPATEN MALANG, JAWA TIMUR - Naufal, Fataa
The research area is located in the administrative district of East Sumbermanjing and the surrounding area of Malang Regency, East Java Province and is located in PT. Perkebunan Nusantara 12 and has an area of 64.3 km2 (6.7 x 9.5 km) and is geographically located at coordinates 9073225-9082740 mU and 687136-693892 mT (WGS84 UTM Zone 49S). Lithotectonically, research areas are part of southern mountains arc of Java which is active in the Oligocene-Miocene period with steep ridge morphology, and is divided into three geomorphological units, Pancursari Lava Flow Ridge Unit, Tambakasri Pyroclastic Flows Ridge Unit and Kedungbanteng Alluvial Valley Unit. Stratigraphy in study area from old to young is composed of 5 lithological units, namely Pyroxene Andesite Lava Unit, Hornblende Andesite Lava Unit, Dacite Lava Unit, Glass Tuff Unit and Alluvial Deposits Unit. The study area is an area with high-sulphidation epithermal deposits system which probably related to porphyry system, consisting of five alteration zones, namely Chlorite- Montmorillonite-Quartz±Epidote Zone, Ilite-Montmorillonite-Chlorite±Calcite Zone, Quartz-Kaolinite-Dickite-Pyrophilite±Alunite Zone, Silicification±Sericite Zone and Unaltered Zone. Alteration and mineralization in the study area is controlled by lithology and faults and fractures on the crater.